Strategi Ketahanan Supply Chain Maritime di Perusahaan Freight Forwarding dengan Pendekatan QFD Berbasis Macroergonomi - Yuliawati, Evi; Mohamad, Silvana; Fasih, Ahmad (Universitas Serang Raya, 2025)
The increasing demand for maritime logistics services requires freight forwarding companies to initiate new ways to operate more efficiently. Business challenges will continue to grow, so companies must balance the quality of logistics services desired by consumers with maritime risks that could disrupt the company's operational performance. This study analyzes the resilience of a freight forwarding company's maritime supply chain. A three-phase Quality Function Deployment (QFD) approach was implemented to develop maritime risk mitigation strategies. The Macroergonomic Analysis of Structure (MAS) perspective involves three elements of the socio-technical system: the technology subsystem, personnel, and external environment. A more optimal work system structure design is hoped to be produced. Integrating the QFD approach based on the MAS perspective resulted in designing maritime supply chain resilience strategies across three subsystem categories. Some of the strategies obtained for each subsystem are as follows: the strategy for the technology subsystem is to implement IT security measures against the potential risk of hacker attacks. The strategy for the personnel subsystem for the top three potential risks is to schedule maintenance for irregular crane maintenance, conduct training for the potential risk of unskilled warehouse operators, and schedule maintenance for the potential risk of irregular truck maintenance. The strategies for the external environment subsystem for the top three potential risks are: designating a maintenance point of contact (PIC) and spare parts for potential crane machine damage, conducting proper maintenance for potential truck machine damage, and obtaining insurance for potential unpredictable road accidents.